Legitimacy of Public Participation in the Establishment of Law in Indonesia: Legitimasi Partisipasi Masyarakat dalam Pembentukan Undang-Undang Di Indonesia - M Nurul Fajri (Jurnal Konstitusi, 2023)
The most participatory form of the public continues, especially since the making process of the omnibus law at Law about Job Creation. Unfortunately, there is no ideal model of public participation. Even though the constitutional court has provided guidelines regarding meaningful participation. There is guaranteed access to public participation, the unanswered question is the aspect of public legitimacy. The review the weaknesses of the public participation model in the formation of the law process in Law about the Establishment of Legislation and Constitutional Court decision. Participation model only answers the formality side, not the substance in the formation of the law, and becomes a validation tool for the academic side, not the aspirations aspect or the legitimacy of the public itself. The problem will be discussed using the normative method. The problem regarding the method of legal development lies in the provisions of the development of the law itself